The effect of timing of influenza vaccination and sample collection on antibody titers and responses in the aged. Issue 30 (27th June 2017) - Kurupati, Raj K.; Kossenkoff, Andrew; Kannan, Senthil; Haut, Larissa H.; Doyle, Susan; Yin, Xiangfan; Schmader, Kenneth E.; Liu, Qin; Showe, Louise; Ertl, Hildegund C.J.
Highlights: Difference in antibody titers after vaccination in aged population. Time of sample collection affected relative numbers of B cell subsets in blood. Collection of samples or timing of vaccination may have misleading influences on study outcome. Abstract: Antibody responses, B cell subset distribution in blood and the blood transcriptome were analyzed in younger and aged human subjects before and after vaccination with the inactivated influenza vaccine. In the aged, but not the younger, individuals we saw a clear difference in antibody titers including those at baseline depending on the time of vaccination and sample collection. Differences in baseline titers in aged individuals treated in the morning or afternoon in turn affected responsiveness to the vaccine. In both younger and aged individuals, the time of sample collection also affected relative numbers of some of the B cell subsets in blood. A global gene expression analysis with whole blood samples from the aged showed small but statistically significant differences depending on the time of sample collection. Our data do not indicate that timing of vaccination affects immune responsiveness of the aged, but rather shows that in clinical influenza vaccine trials timing of collection of samples can have a major and potentially misleading influence on study outcome. In future vaccine trials, timing of vaccination and sample collection should be recorded carefully to allow for its use as a study covariant.